If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4-(7d+8)=6
We simplify the equation to the form, which is simple to understand
4-(7d+8)=6
Remove unnecessary parentheses
4-7d-8=6
We move all terms containing d to the left and all other terms to the right.
-7d=+6-4+8
We simplify left and right side of the equation.
-7d=+10
We divide both sides of the equation by -7 to get d.
d=-1.4285714285714
| 0=-3(x^2+2x) | | 8(x+2)=(2x+16) | | 2n+(-3)4=28 | | -2x-5x=-7 | | 5x+0.2=2X-0.34 | | 670-P=63 | | 2(2x-8)=9(x+1) | | -x-4x=15 | | 8(x+2)=(2x-1) | | 1s+7=90 | | x^3-3x^2-24x+12=0 | | 2(4n-8)-2n=10 | | 4p+4p=16 | | 7/2x=10 | | x+2+1=4 | | 78=5(2x+4)-8x | | z+6+4z-9+8u= | | -6t^2+72t+40=0 | | 3(x+8)=2(2x+14) | | 0=-3x^2-6x | | 6h-213=747 | | 256=7x-11 | | 2b=4b-6 | | 8+5x=2 | | X^5+16x^3+60x=0 | | 278=x^4 | | 20x+14y=17 | | 4a-10=-14 | | x/(x=2)=4/5 | | 3(x-0.80)=4x+4 | | -1=1x-2 | | 7x-101=61+13x |